Gambaran Psikologis Pejabat Fungsional Pustakawan Sebagai Petugas Layanan Perpustakaan pada Masa Pandemi COVID-19 di Provinsi Riau - Thamrin Hasan; Hadriani; Yurnalis (Perpustakaan Universitas Riau, 2021)
The COVID-19 pandemic has caused tremendous psychological symptoms. Psychological symptoms are not only experienced by library management officers, but also experienced by service officers in other fields. The question should be asked, what is the psychological picture of the librarian in carrying out his duties as a library service? This is worth knowing. The purpose of this study was to determine the psychological picture of librarians as library service officers during the COVID-19 pandemic. The study uses a descriptive method. The sample studied was 94 librarians. Full sampling technique (total sampling). The research instrument used a questionnaire with a Likert scale model. The data analysis technique used descriptive statistical analysis. The results of the research as a whole show that the psychological picture of librarians obtained a total mean value of 4.35. This total mean score is on an interval scale of 4.24 – 5.04. This shows that the psychological picture of the librarian is the category of never experiencing a psychological mental disorder. The level of the librarian's psychological picture is generally positive. The results of this study are useful for improvement and improvement in setting library service strategies, especially during the COVID-19 pandemic in Riau Province. The conclusion of the study shows that the psychological level description is in the positive category. This means that the attitudes, behaviors and actions of the librarian in carrying out their duties psychologically do not experience deviations.